ESTRATÉGIAS DE EXPANSÃO DE INSTITUIÇÕES DE ENSINO SUPERIOR PRIVADAS NO BRASIL: ESTUDO DE CASO DO CURSO DE BACHARELADO EM ADMINISTRAÇÃO - PRADO, SONIA REGINA (2016)
This dissertation presents an analysis of a Brazilian Private Higher Education Institution (IES) growth after the establishment of the Lei de Diretrizes e Bases (LDB), from 1996 to 2015, through the bachelor's program in Business Administration, in different modes: traditional classes, distance learning and semi-distance education. In order to do this, it was performed an exploratory research, based on qualitative methods and case studies. The material was colleted from corporate reports (Annual Report, internal reports and other documents), semi-structured interviews with managers of IES and observations. The key findings of this study were that the main strategies chosen by the institution in order to grow in this market were based on mergers and acquisitions of other IES, opening of new distance learning centers, the opening of new educational units as well as innovative ideas in different areas of the organization. Government funding programs to students are also significant contributors to this growth, such as the Fundo de Financiamento ao Estudante do Ensino Superior (FIES) and the Programa Universidade para Todos (Prouni). In this new reality, the specific institution had the most important incentive plan to encourage and facilitate its growth, in an accelerated way. As a result, the conclusion is that the institution employs the following growth strategies: organic expansion with mergers/acquisitions of smaller institutions, which includes development plans for all campuses in Brazil; Greenfield (through the request of new units and/or courses) in cities where there is no potential acquisitions/mergers; and the increase in the number of places/enrollment in the universities, associated to the participation in the public financing programmes. The IES also implemented actions in order to decrease drop-out rates, such as educational insurance; managers prepared to meet student needs; an educational system with national and integrated curriculum; higher education cooperation including exchanges of students and professors all over the country and the standardization of processes.